PELATIHAN KOMPOSTING SAMPAH SKALA RUMAH TANGGA DALAM PENGELOLAAN SAMPAH BERBASIS MASYARAKAT DESA KETEGAN TANGGULANGIN SIDOARJO - Ermavitalini, Dini; Jadid, Nurul; Muslihatin, Wirdhatul; Saputro, Triono Bagus; Shovitri, Maya; Prasetyo, Endry Nugroho; Sa’adah, Noor Nailis; Purwani, Kristanti Indah (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2019)
Along with the increasing number of people and all economic activities carried out, waste becomes acontamination that continues to leave problems. Sidoarjo Regency has 18 sub-districts with 350 villagesand a population of around 2.3 million people with a high level of economic growth. According to the 2017Sidoarjo Regency Environmental and Hygiene Office (DLHK), reported that Sidoarjo district residentsdispose of household waste around 0.5 kg per day. DLHK identifies the lack of Integrated WasteManagement Sites (TPST) and Final Waste Disposal Sites (TPAS) to accommodate and manage wastefrom the Sidoarjo Regency community. The lack of TPST and TPAS is not a problem in wastemanagement if active community involvement is involved in processing household waste known asCommunity Based Waste Management (PSBM). This abdimas method is a campaign about theimportance of the role of the community in improving environmental status and composting training withraw materials in the form of kitchen waste with a simple household-scale tool located in the KeteganVillage office, Tanggulangin Sub-district, Sidoarjo. The participants were very enthusiastic about takingpart in the training and were eager to practice household composting on a household scale for the need tofertilize plants planted in the yard. Participants want monitoring by the service team on the compostingresults that have been carried out by each participant.